2016
DOI: 10.1590/s1806-92902016000900008
|View full text |Cite
|
Sign up to set email alerts
|

Dietary glycerin does not affect meat quality of Ile de France lambs

Abstract: -The objective of this study was to evaluate the physicochemical and nutritional characteristics of meat from three muscles of Ile de France lambs fed diets containing different levels of glycerin as an alternative to corn. Thirty non-castrated feedlot Ile de France lambs weighing 15±0.2 kg were housed in individual pens and slaughtered at 32±0.2 kg. Treatments consisted of three diets: sugarcane + 0% glycerin; sugarcane + 10% glycerin; and sugarcane + 20% glycerin; and three muscles were evaluated: triceps br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
6
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 32 publications
4
6
1
1
Order By: Relevance
“…The FA profile of the control groups was dominated by SFAs (53–57%), followed by MUFAs (39–43%), and then PUFAs (3–4%), while the PUFA/SFA ratio reached 0.06. These results are in agreement with other authors’ findings for Suffolk and Ile de France meat (Borghi et al, 2016; Romero‐Bernal et al ., 2016). However, the PUFA content increased significantly ( P ≤ 0.05) after all meat treatments; MUFAs reduced in all the treated Suffolk samples, while the SFAs decreased in both breeds of lamb meat after treatment with ThyEO.…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…The FA profile of the control groups was dominated by SFAs (53–57%), followed by MUFAs (39–43%), and then PUFAs (3–4%), while the PUFA/SFA ratio reached 0.06. These results are in agreement with other authors’ findings for Suffolk and Ile de France meat (Borghi et al, 2016; Romero‐Bernal et al ., 2016). However, the PUFA content increased significantly ( P ≤ 0.05) after all meat treatments; MUFAs reduced in all the treated Suffolk samples, while the SFAs decreased in both breeds of lamb meat after treatment with ThyEO.…”
Section: Resultssupporting
confidence: 94%
“…The cholesterol values obtained for Suffolk and Ile de France meat were similar to the results of Borghi et al (2016); however, they were lower than those found by Vecvagars et al (2018) in the same lamb breeds. The cholesterol level in lamb meat is strongly influenced by breed and usually correlates with an increased SFA content (Attia et al, 2017;Aksoy et al, 2019).…”
Section: Biogenic Amines In Lamb Meatsupporting
confidence: 85%
“…The sarcomere length of 1.60 mM observed in this study (Table 4) was close to the 1.72 mM mentioned by Borghi et al (2016), who evaluated the Longissimus lumborum of feedlot-finishedÎle-de-France lambs; to the 1.70 mM reported by Oliveira et al (2004) with Santa Inês lambs and sheep; and to the 1.67 mM observed by Silva Sobrinho et al (2005) in Romney  East Friesian  Poll Dorset lambs. Sarcomeres are the myofibril units responsible for the muscular contraction.…”
Section: Resultssupporting
confidence: 89%
“…In this study, the pH and WHC of the meat from animals fed control diet did not differ from the other treatments, and the type of fiber analyzed was the same for all animals. According to the literature, the by-products used in this study do not promote changes in the SF of sheep and beef meat (LAGE et al, 2014;CARVALHO et al, 2015;BEZERRA et al, 2016;BORGHI et al, 2016), reinforcing the unexpected pattern of SF in this work.…”
Section: Discussionsupporting
confidence: 69%